Analisis Pengaruh Penerapan Green Accounting terhadap Kinerja Perusahaan Manufaktur dalam Bursa Efek Indonesia - Sparta Sparta (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2022)
This study aims to determine the effect of the application of green accounting on the performance of companies in the manufacturing sector. Green accounting is measured by environmental cost and environmental performance which are independent variables in this study. Meanwhile, company performance is measured by financial performance as proxied by ROA and company value as proxied by PER. This study was conducted on manufacturing companies that are PROPER participants and listed on the Indonesia Stock Exchange (IDX) for the period 2014 – 2019. This study uses multiple regression analysis to test this hypothesis. The sample in this study used purposive sampling method to obtain a sample of 120 companies in the manufacturing sector. The results of the first equation in this study indicate that environmental cost has no effect on financial performance and environmental performance has a positive influence on financial performance. While the results of the second equation in this study indicate that environmental cost has a positive effect on firm value and environmental performance has a negative effect on firm value. Suggestions for further research is to conduct research on other sectors on the IDX with the latest period so that the results obtained can provide an overview of the application of green accounting in each sector of different companies and get more accurate results